2010
DOI: 10.1186/1751-0147-52-37
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between antibody status to bovine corona virus and bovine respiratory syncytial virus and disease incidence, reproduction and herd characteristics in dairy herds

Abstract: BackgroundBovine respiratory syncytial virus (BRSV) and bovine corona virus (BCV) affects cattle worldwide. Our objective was to evaluate the effects of these infections on general health and reproduction parameters measurable on herd level and to explore the association between antibody status and some herd characteristics.MethodsWe collected a pooled milk sample from five primiparous cows from 79 Swedish dairy herds in September 2006. The samples were analysed for immunoglobulin G antibodies to BCV and BRSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
14
1
1
Order By: Relevance
“…As mentioned, PostPFree relates to presence of antibodies and not necessarily presence of virus. Ideally, one would prefer to use a test detecting the antigen itself in order to achieve a herd's true infection status; however, this is demanding to do on a large scale, and antibody testing is commonly used (Hägglund et al, 2006;Beaudeau et al, 2010;Ohlson et al, 2010a). Animal purchase might mean introducing an antibody positive animal and not necessarily introducing virus.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, PostPFree relates to presence of antibodies and not necessarily presence of virus. Ideally, one would prefer to use a test detecting the antigen itself in order to achieve a herd's true infection status; however, this is demanding to do on a large scale, and antibody testing is commonly used (Hägglund et al, 2006;Beaudeau et al, 2010;Ohlson et al, 2010a). Animal purchase might mean introducing an antibody positive animal and not necessarily introducing virus.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that BRSV is circulating between herds throughout the year, which is important knowledge for outlining strategies to prevent the inter-herd spread of BRSV. Control of BRSV can be achieved by improved biosecurity measures [28] or vaccination. Live and inactivated vaccines against BRSV are used around the world, but their efficiency has been questioned [12,27,37].…”
Section: Discussionmentioning
confidence: 99%
“…A high herd prevalence of BRSV was also reported in Danish dairy herds [26], and the infection is regarded as one of the most important welfare and economic problems in the Danish beef industry, associated with a high mortality among calves and a high rate of antibiotic treatment [27]. Studies have shown that there are negative effects associated with BRSV infections on herd health and animal performance [22,28] and an association between a high biosecurity level and lower herd prevalence [23]. There is, however, limited information about similarity and evolutionary relationship among the BRSV strains in the Swedish cattle population.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-herd transmission usually occurs by aerosols, allowing the virus to enter susceptible cattle via the respiratory tract. However, local spread and airborne transmission between herds are not of great importance for inter-herd transmission despite the circulation of BRSV in a given geographical region [8]. On the other hand, direct transmission between herds is frequently a consequence of the introduction of new infected animals, while indirect transmission occurs by individuals visiting farms.…”
Section: Epidemiology Of Brsvmentioning
confidence: 99%
“…Some of the main risk factors for BRSV transmission include large herd size and common farm practices such as not providing boots to visitors and dual-purpose farms [9,10]. Additionally, it has also been proposed that good management and better hygienic routines have a direct impact on overall health status [8]. …”
Section: Epidemiology Of Brsvmentioning
confidence: 99%